2014
DOI: 10.3390/rs6109379
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of SAR Sea Clutter for Classification Purposes

Abstract: Statistical analysis of radar clutter has always been one of the topics, where more effort has been put in the last few decades. These studies were usually focused on finding the statistical models that better fitted the clutter distribution; however, the goal of this work is not the modeling of the clutter, but the study of the suitability of the statistical parameters to carry out a sea state classification. In order to achieve this objective and provide some relevance to this study, an important set of mari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…For the Gamma distribution, the scale parameter monotonously increases with ACW while the shape parameter decreases with PBR. This result is consistent with the result of [32]. Meanwhile, the increase in PBR results in the expanding range of the scale parameter for the Gamma and Weibull distributions.…”
Section: Evaluation Of the Goodness-of-fit Of Pdf Models With Sea Stasupporting
confidence: 91%
See 2 more Smart Citations
“…For the Gamma distribution, the scale parameter monotonously increases with ACW while the shape parameter decreases with PBR. This result is consistent with the result of [32]. Meanwhile, the increase in PBR results in the expanding range of the scale parameter for the Gamma and Weibull distributions.…”
Section: Evaluation Of the Goodness-of-fit Of Pdf Models With Sea Stasupporting
confidence: 91%
“…The current study statistically investigated the dependence of the PDF parameters on the properties of sea states, including the ACW and PBR. By analyzing a limited number of TerraSAR-X scenes, [32] showed that the distribution parameters could be used for sea state classification. Their results are confirmed by the further detailed sensitivity analysis of the present study using SAR images with a variety of sea states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors such as speckle noise, bathymetry or wind changed marine discontinuities, oil spills, ship wakes and harbor areas may cause the non-uniform ocean surface [1,2]. Whereas, various sea clutter describing approaches have been available in the literature, it remains an open and challenging problem which greatly restricts the performance of constant false alarm rate (CFAR) based ship detection algorithms [3,4].…”
Section: Dear Editormentioning
confidence: 98%
“…Many other parametric distributions have been proposed to model radar sea clutter; see the reviews [47,48]. The ones mostly used are Gaussian [12], log-normal and Weibull [44,49,50].…”
mentioning
confidence: 99%